2016
DOI: 10.1038/aps.2015.127
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the channel gating of P2X receptors from structures, dynamics and small molecules

Abstract: P2X receptors, as ATP-gated non-selective trimeric ion channels, are permeable to Na + , K + and Ca 2+ . Comparing with other ligand-gated ion channel families, P2X receptors are distinct in their unique gating properties and pathophysiological roles, and have attracted attention as promising drug targets for a variety of diseases, such as neuropathic pain, multiple sclerosis, rheumatoid arthritis and thrombus. Several small molecule inhibitors for distinct P2X subtypes have entered into clinical trials. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 139 publications
0
23
0
Order By: Relevance
“…Recently, a number of crystal structures representing different P2X receptor isoforms and active states were made available (9-11, 18, 28, 29). These structures suggest that multiple allosteric changes may be associated with ATP binding to channel gating (27,(30)(31)(32)(33)(34)(35), and, presumably, each of the allosteric changes can be targeted by small molecules for functional perturbation. However, it remains challenging to define the function of a potential allosteric site, identify the drug, and determine the drug's mechanism of action at the specific site (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a number of crystal structures representing different P2X receptor isoforms and active states were made available (9-11, 18, 28, 29). These structures suggest that multiple allosteric changes may be associated with ATP binding to channel gating (27,(30)(31)(32)(33)(34)(35), and, presumably, each of the allosteric changes can be targeted by small molecules for functional perturbation. However, it remains challenging to define the function of a potential allosteric site, identify the drug, and determine the drug's mechanism of action at the specific site (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Out of these seven receptors, P2RX2 is an ATP-gated trimeric ion channel that plays an important role in sound transduction and auditory neurotransmission in the inner ear (Housley et al, 2002 , 2013 ; Järlebark et al, 2002 ; Wang et al, 2003 ; Yan et al, 2013 ). ATP binding to the extracellular loop of the channel is thought to cause conformational changes that trigger channel pore opening and cation internalization (North, 2002 ; Roberts et al, 2006 ; Stelmashenko et al, 2012 ; Mittal et al, 2016 ; Wang and Yu, 2016 ). However, it is not known whether ATP binding or hydrolysis is required for the P2X2 activation.…”
Section: Introductionmentioning
confidence: 99%
“…The structural comparison of the closed and open structures suggests a possible gating mechanism of P2X receptors (Fig. 1, A and B) (9,16,23,24). First, at the ATP-binding site, ATP promotes the jaw closure between the head and dorsal fin (DF) 3 domains, making the DF domain move upward to the head domain to accommodate ATP.…”
mentioning
confidence: 99%
“…Recent studies (22,31) also suggested that the TM region was distorted due to the unexpected absence of intersubunit interactions in the X-ray open structure of zfP2X4 receptor. Thus, although the apo/closed and ATP-bound open X-ray structures of the zfP2X4 receptor have provided a blueprint for the mechanism of P2X activation, the detailed conformational transition during channel gating requires further exploration (18,22,24,31,32,37,39,40).…”
mentioning
confidence: 99%